Automatic Flavored Drinking Water Maker - Selvam, NavenKumar; Hazli Roslan (Progress in Engineering Application and Technology, 2024)
This project introduces an innovative Automatic Flavored Drinking Water Maker designed to streamline the process of creating customized flavored beverages. Utilizing RFID card authentication, users can access a menu of beverage options by scanning their unique cards. The system supports the dispensing of three distinct drinks: syrup, lime, and lemon syrup, with an optional sugar addition. A user-friendly interface, featuring buttons and an LCD display, guides the selection process. The core functionality is orchestrated through an Arduino-based microcontroller, which controls relays responsible for dispensing precise amounts of each ingredient. Ultrasonic sensors monitor liquid levels, ensuring accuracy and preventing overflows. The system incorporates timers for sequential ingredient release, providing a seamless and automated user experience. Visual and auditory feedback, including LEDs and a buzzer, enhance user interaction and convey the system's status. The project not only offers a convenient and hygienic solution for personalized drink preparation but also integrates real-time monitoring of liquid percentages, displayed on the LCD. This paper details the system's architecture, sensor integration, control mechanisms, and the overall user experience, contributing to the advancement of automated beverage dispensing systems